САЛИҲ БИШАКЧИ ТOМOНИДАН АБДУРАУФ ФИТРАТ АСАРЛАРИНИНГ ҚИЁСИЙ ТАҲЛИЛИ (Scientific journal of the Fergana State University, 2023)
In this article described the interpretation of Abdurauf Fitrat’s literary inheritance by foreign scholars, especially by the Turkish literary critic Salih Bishakchi